Trends in the cost of medicines, consultation fees and clinic visits in Malaysia’s private primary healthcare system: employer health insurance coverage - Zin, Che Suraya; Ab Rahman, Norny Syafinaz; Mohamed Nazar, Nor Ilyani; Kurdi, Amanj; Godman, Brian (Dove Medical Press, 2023)
Objective: To examine trends in the cost of medicines, consultation fees and clinic visits among the employees covered by the employer health insurance in Malaysia’s private primary healthcare system in Malaysia. Designs: Retrospective cross-sectional study. Setting: PMCare claims database from January 2016 to August 2019.mParticipants: A total of 83,556 outpatient clinic visits involving 10,150 IIUM employees of the International Islamic University Malaysia (IIUM) to private general practitioners (GPs). During the study period, IIUM adopts the incentive structure of capping coverage at Ringgit Malaysia (RM) 45/outpatient visit (USD 10.58) to cover for consultation fees and medicine costs. Main Outcome Measures: The monthly percentage change in the number of clinic visits, medicine costs, consultation fees and total costs between January 2016 and August 2019. A simple linear regression using Stata v15.1 was also performed to measure the association between the characteristics of the prescribed medicines and medicine charges. Results: The number of clinic visits per patient increased by 17% from January 2016 to August 2019, with consultation fees increasing by 113.9% and total costs by 7.9% per clinic visit per patient. Conversely, the cost of medicines and the number of medicines prescribed per clinic visit per patient decreased by 39.7% and 6.3%, respectively. Conclusion: Within the incentive structure of capping the total amount of coverage per clinic visit, medicine costs were reduced by decreasing the number of medicines prescribed, to offset the increased consultation fees. This may create perverse incentives that affect medicine use with negative consequences for the health system and health insurers.